2021
DOI: 10.1101/2021.09.30.462488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Durability of immune responses to the BNT162b2 mRNA vaccine

Abstract: The development of the highly efficacious mRNA vaccines in less than a year since the emergence of SARS-CoV-2 represents a landmark in vaccinology. However, reports of waning vaccine efficacy, coupled with the emergence of variants of concern that are resistant to antibody neutralization, have raised concerns about the potential lack of durability of immunity to vaccination. We recently reported findings from a comprehensive analysis of innate and adaptive immune responses in 56 healthy volunteers who received… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“… 11 In serum from individuals immunized with Ad26.COV2.S, mRNA-1273, or BNT162b2 vaccines, difference in neutralization comparing historical and B.1.621 SARS-CoV-2 ranged from 2.1- to 8.7-fold depending on the study population and vaccine. 12 , 13 , 14 , 15 , 16 A similar difference (4.7- to 12-fold) in neutralization was observed in convalescent sera from previously infected individuals. 13 , 14 However, the impact of the spike mutations in B.1.621 on the protective efficacy of vaccines in vivo remains unknown.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“… 11 In serum from individuals immunized with Ad26.COV2.S, mRNA-1273, or BNT162b2 vaccines, difference in neutralization comparing historical and B.1.621 SARS-CoV-2 ranged from 2.1- to 8.7-fold depending on the study population and vaccine. 12 , 13 , 14 , 15 , 16 A similar difference (4.7- to 12-fold) in neutralization was observed in convalescent sera from previously infected individuals. 13 , 14 However, the impact of the spike mutations in B.1.621 on the protective efficacy of vaccines in vivo remains unknown.…”
Section: Introductionsupporting
confidence: 65%
“…In sera from vaccinated or infected individuals, the fold difference in neutralization between the D614G (B.1) variant of SARS-CoV-2 and B.1.621 was between 2- and 12-fold. 12 , 13 , 14 , 15 , 16 , 32 In Syrian hamsters, we observed a ∼3-fold decrease (p < 0.001) in serum neutralization titers between the WA1/2020 and B.1.621 virus. In K18-hACE2 mice immunized with mRNA-1273, the difference in serum neutralization titers between WA1/2020 N501Y/D614G and B.1.621 was 1.3- to 2.3-fold.…”
Section: Discussionmentioning
confidence: 65%
“…These results contrast with a recent longitudinal study in humans immunized with mRNA-1273, which showed lower neutralizing titers of serum antibody against B.1.351 than other VOC, including B.1.617.2, although those data were collected using pseudovirus rather than live virus neutralization assays ( 23 ). Another study using a live virus neutralization assay and human serum obtained three weeks post immunization with the BNT162b2 mRNA vaccine also showed lower neutralizing titers against B.1.351 than B.1617.2, though this trend reversed at 6 months ( 24 ). In our experiments with live virus, the loss of neutralizing activity was equivalent if not greater for B.1.617.2 than B.1.351, as reported by others with human serum samples from individuals infected with B.1.351 or P.1 ( 25 ).…”
Section: Discussionmentioning
confidence: 97%
“…These data confirm waning immunity to mRNA vaccination against SARS-CoV-2 in the golden Syrian hamster, as was shown recently after natural infection 28,29 . The similarity to which serum NAb titers were generated and then waned relative to humans provides support for the hamster as a high-fidelity model for studying booster vaccination 30,31 .…”
Section: Main Textmentioning
confidence: 99%